The Diagnostic Challenge Posed By Cardiac Myxomas: A Quintessential Case - Saad Warraich, Abdullah Al-Hudaib (International Journal of Innovative Research in Medical Science, 2017)
Cardiac myxoma is the commonest of a rare group of entities known as benign growths of the heart. This case report aims to highlight the challenges associated with diagnosing a patient with this tumour. The discovery in our patient was unexpectedly made when an echocardiography study was conducted to investigate persistent dyspnea. After its detection, the tumour was consequently surgically resected. Most cases, like this one, are incidental findings. Patients usually present with episodic dyspnea, hemoptysis, syncope, signs of right heart failure, ascites, or hepatic congestion. Due to the unique characteristics of the tumour, echocardiography remains the ideal method for investigation. The diagnosis, however, is confirmed only by biopsy.